Impact of elexacaftor–tezacaftor–ivacaftor on bacterial colonization and inflammatory responses in cystic fibrosis - Sheikh, Shahid; Britt, Rodney D.; Ryan‐Wenger, Nancy A.; Khan, Aiman Q.; Lewis, Brandon W.; Gushue, Courtney; Ozuna, Hazel; Jaganathan, Devi; McCoy, Karen; Kopp, Benjamin T. (Pediatric pulmonology, 2023)
Background Cystic fibrosis (CF) is a multisystem disease with progressive deterioration. Recently, CF transmembrane conductance regulator (CFTR) modulator therapies were introduced that repair underlying protein defects. Objective of this study was to determine the impact of elexacaftor–tezacaftor–ivacaftor (ETI) on clinical parameters and inflammatory responses in people with CF (pwCF). Methods Lung function (FEV1), body mass index (BMI) and microbiologic data were collected at initiation and 3‐month intervals for 1 year. Blood was analyzed at baseline and 6 months for cytokines and immune cell populations via flow cytometry and compared to non‐CF controls. Results Sample size was 48 pwCF, 28 (58.3%) males with a mean age of 28.8 ± 10.7 years. Significant increases in %predicted FEV1 and BMI were observed through 6 months of ETI therapy with no change thereafter. Changes in FEV1 and BMI at 3 months were significantly correlated (r = 57.2, p < 0.01). There were significant reductions in Pseudomonas and Staphylococcus positivity (percent of total samples) in pwCF through 12 months of ETI treatment. Healthy controls (n = 20) had significantly lower levels of circulating neutrophils, interleukin (IL)‐6, IL‐8, and IL‐17A and higher levels of IL‐13 compared to pwCF at baseline (n = 48). After 6 months of ETI, pwCF had significant decreases in IL‐8, IL‐6, and IL‐17A levels and normalization of peripheral blood immune cell composition. Conclusions In pwCF, ETI significantly improved clinical outcomes, reduced systemic pro‐inflammatory cytokines, and restored circulating immune cell composition after 6 months of therapy.